2003
DOI: 10.1046/j.1095-8339.2003.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetics and evolution of Orchidinae and selected Habenariinae (Orchidaceae)

Abstract: Internal transcribed spacer (ITS nuclear rDNA) data have been obtained from 190 terrestrial orchid species, encompassing all genera and the great majority of the widely recognized species of Orchidinae, a heterogeneous selection of species of Habenariinae, and single species of Satyriinae and Disinae (the latter serving as outgroup). The resulting parsimony‐based phylogeny reveals 12 well‐resolved clades within the Orchidinae, based on Anacamptis s.l., Serapias, Ophrys, Steveniella–Himantoglossum s.l. (includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
430
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(472 citation statements)
references
References 74 publications
37
430
1
4
Order By: Relevance
“…This sharing of individual pollinators is not restricted to distantly related orchid species. For example, hemipollinaria of the closely related species O. mascula and O. pauciflora, as indicated by phylogenetic studies (Cozzolino et al 2001;Bateman et al 2003), were found on the same individual insect (Bombus humilis), confirming the occurrence of pollinator sharing also among orchid sister-species.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This sharing of individual pollinators is not restricted to distantly related orchid species. For example, hemipollinaria of the closely related species O. mascula and O. pauciflora, as indicated by phylogenetic studies (Cozzolino et al 2001;Bateman et al 2003), were found on the same individual insect (Bombus humilis), confirming the occurrence of pollinator sharing also among orchid sister-species.…”
Section: Discussionmentioning
confidence: 71%
“…The latter would imply that these temperate orchid species have evolved alternative reproductive isolation mechanisms for maintaining species boundaries. Today, a well-supported phylogenetic framework for the European Orchidinae is available (Cozzolino et al 2001;Bateman et al 2003), which can be used for investigating pollinator specificity at varying levels of phylogenetic relatedness.…”
Section: Introductionmentioning
confidence: 99%
“…and Graebn.). In a phylogenetic tree based on an internal transcribed spacer (ITS) both species are distantly related (Bateman et al 2003). We would, therefore, like to propose the hypothesis of a fooddeception mechanism between flowers of G. conopsea (as a rewarding model) and A. pyramidalis (as a non-rewarding mimic) according to Batesian floral mimicry.…”
Section: Discussionmentioning
confidence: 99%
“…The latter were based on a phylogeny of the 19 study species (table 1) obtained from existing phylogenetic trees (Cameron et al 1999;Bateman et al 2003) trimmed to include just the 19 species of interest. Branch lengths were assigned according to Pagel's arbitrary method (Pagel 1992).…”
Section: Methodsmentioning
confidence: 99%